0
$\begingroup$

Pretty simple question that I never thought id get stuck on. How do I factor $x^2 - 6x + 8 - d$ into a form $(x - a)(x - b)$ where $d$ is just an unknown constant ? Been looking online but it seems all the tutorials / videos but have not found anything useful.

EDIT: Im silly for not remembering the formula $x = \dfrac{-b \pm \sqrt{b^2 - 4ac}}{2a} $

$\endgroup$
  • 3
    $\begingroup$ Hint: use the quadratic formula. $\endgroup$ – lulu Apr 18 '18 at 20:23
  • $\begingroup$ Doh ! Im an idiot for not remembering that.. Thanks... $\endgroup$ – Kong Apr 18 '18 at 20:24
  • $\begingroup$ Note that the $c$ in the quadradic formula is $c = 8-d$ in your expression. That is, $a=1, b= -6, c=8-d$. $\endgroup$ – amWhy Apr 18 '18 at 20:29
0
$\begingroup$

$x^2 + x(a + b) + ab = (x + a)(x + b)$

then,

$x^2 - 6x + 8 - c = (x + a)(x + b)$ , where

$ab = 8 - c$

$a + b = -6$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.